2019
DOI: 10.1111/jcmm.14334
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐human CD9 antibody Fab fragment impairs the internalization of extracellular vesicles and the nuclear transfer of their cargo proteins

Abstract: The intercellular communication mediated by extracellular vesicles ( EV s) has gained international interest during the last decade. Interfering with the mechanisms regulating this cellular process might find application particularly in oncology where cancer cell‐derived EV s play a role in tumour microenvironment transformation. Although several mechanisms were ascribed to explain the internalization of EV s, little is our knowledge about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 64 publications
0
30
0
1
Order By: Relevance
“…As reported for apoptotic bodies or certain viruses, phosphatidylserine present at the outer leaflet of EV membrane can play a role in their cellular entry [ 88 , 89 , 90 ]. We showed that monovalent antibody against CD9 can impede the entry of EVs into melanoma cells [ 91 ]. Further efforts are needed to dissect all mechanisms regulating the specificity of EV-recipient cell interactions, which is an important step to design new strategies based on EVs as a bio-vehicle for therapeutic drug delivery [ 92 , 93 , 94 ].…”
Section: Extracellular Membrane Vesicles and Intercellular Communimentioning
confidence: 99%
See 1 more Smart Citation
“…As reported for apoptotic bodies or certain viruses, phosphatidylserine present at the outer leaflet of EV membrane can play a role in their cellular entry [ 88 , 89 , 90 ]. We showed that monovalent antibody against CD9 can impede the entry of EVs into melanoma cells [ 91 ]. Further efforts are needed to dissect all mechanisms regulating the specificity of EV-recipient cell interactions, which is an important step to design new strategies based on EVs as a bio-vehicle for therapeutic drug delivery [ 92 , 93 , 94 ].…”
Section: Extracellular Membrane Vesicles and Intercellular Communimentioning
confidence: 99%
“…Lastly, the discovery of nucleoplasmic reticulum-associated late endosomes might open new avenues to deliver and target specific drugs to nuclei of cancer cells or other pathologic cells. Altogether, deciphering at a molecular level all spatiotemporal multi-steps of this new intracellular pathway would benefit the field of nanobiological technology towards new medical therapeutic approaches [ 91 ].…”
Section: Perspectives and Future Directionsmentioning
confidence: 99%
“…As these two antibodies were not specific to the tumor-derived EVs, the authors explained this result by a general decrease in EV flux between organs, including the tumor, and demonstrated that these antibodies stimulated the uptake of EVs by patrolling macrophages. It was also demonstrated that the use sof a fragment of CD9-antibody could prevent the transfer of tumor-derived EV cargoes in recipient cells in vitro [ 101 ]. We previously demonstrated that obese patients have higher levels of circulating EVs in comparison to healthy patients [ 100 ], suggesting increased deleterious cross-talk between metabolic organs, including WAT.…”
Section: Therapeutic Strategies To Decrease Ad Ev Deleterious Effementioning
confidence: 99%
“…In addition to being a direct cellular target, CD9 can be indirectly used to interfere with EV-mediated intercellular communication between cancer cells and their surrounding microenvironment. Given that anti-CD9 Ab can favor the CD9 dimerization and its internalization, oligomerization with its interacting partners or promote the ligation between cells (see below), 54,109,184,185 we designed a new strategy to block the endocytosis of cancer-derived CD9-positive EVs by recipient/receptor cells notably stromal cells, the target cells in the tumor microenvironment. To that aim, we generated an antigen-binding fragment (Fab fragment) from an anti-CD9 Ab (5H9).…”
Section: Cd9 As a Target Of Tumor Angiogenesis And Cancermentioning
confidence: 99%